Analysis Of Time Motion Study Comparison For Coconut Husk Processing With Coconut Husk Crushing Machine Assistive Tool - Hermawan, Andri; Trisolvena, Muhammad Nana; Nurudin, Arif (Jurnal Improsci, 2025)
Background. Entrepreneurs utilize abundant raw materials by making coconut husk, which is the main ingredient in making coconut husk brooms. However, many still use conventional methods to process it, such as pounding it until it becomes fiber. Aim. To be carried out effectively, it is deemed necessary to have technological assistance, such as the Coconut Husk Shredding Machine. Methods. However, to ensure that the aid has improved the effectiveness of the coconut husk shredding process, it is necessary to analyze and compare the time motion study between the two methods. By comparing the Standard Time between the two methods, Result. We can determine the extent of the difference, allowing us to quickly estimate the amount of product produced from coconut husk shredding within a specific time frame or how long it takes to process the available amount of coconut husk. Conclusion. The research and time motion study analysis results in an activity of shredding coconut husks using conventional methods and machines, which aligns with the hypothesis that shredding coconut husks using machines is 2.91 minutes faster than traditional methods. Implication. This work time measurement recommendation can be used as a standard time measurement in shredding coconut husks using conventional and machine methods.